Fostering Tolerance and Respect for Diversity through the Fundamentals of Islamic Education - Aderibigbe, Semiyu Adejare; Idriz, Mesut; Alzouebi, Khadeegha; AlOthman, Hussain; Hamdi, Wafa Barhoumi; Companioni, Assad Asil (Religions (Basel, Switzerland ), 2023)
Societies are getting more diverse, with social issues increasing, necessitating the need to intensify efforts to promote tolerance and respect for diversity. In this study, we report the approach employed to redesign and evaluate a general education course to enhance students’ knowledge of tolerance and respect for diversity, drawing on Islamic values in the United Arab Emirates. In collecting and analyzing data for the study, we adopted a qualitative approach to explore students’ nuanced and reflective understanding and application of the key concepts taught in the course. We retrieved and thematically analyzed 40 transcripts from sixty-nine students’ reflective assignments. Our results indicate that students see the education process based on Islamic principles as a socialization means for shaping human life, caring for others, demonstrating compassion, and sharing knowledge, as essential to fostering tolerance. Drawing on our findings, we recommend carefully redesigning courses to strengthen students’ knowledge of tolerance and respect for diversity using the authentic learning approach. This includes engaging them in activities to link class tasks to real-life contexts, providing them with safe learning spaces, and encouraging them to learn with peers from different backgrounds.